Reminiscences by a Historian of Southeast Asia - Watson-Andayana, Barbara (Jurnal Mengkaji Indonesia, 2024)
This presentation had several goals. The first was to provide a sense of the ways in which the field of Southeast Asia studies, especially history, has developed during my own career, especially during the 1960s. A second goal was to address the tension between country-based history and comparisons across the region. Third, I described the decline in Southeast Asian studies in the 1980s and 90s and the new questions that arose as global histories assumed greater prominence. A fourth goal was to highlight the rise of women’s history, although this tended to focus on the late 19th and 20th centuries. The identification of the early modern period as a focus of historical interest opened a door to thinking comparatively about the role of women during a time of regional change. The talk ended with comments about the apparent decline of history in the United States and the expectation that the study of the past, so fundamental to national and regional identities, will be maintained in Southeast Asia.